Gambaran Tingkat Pengetahuan Masyarakat Tentang Vaksinasi Covid-19 pada Anak RS Dr Sumantri Parepare 2022 - Wahyuni L. Ode; Hawa Hawa; Annisa Rahmawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
An abstract is a brief summary of a paper to help readers quickly ascertain the purpose of the study and according to research needs. Abstracts must be clear and informative, provide a statement for the problem under study and the solution. The abstract length is between 90 and 230 words. Avoid unusual abbreviations and define all symbols used in abstracts. Using keywords related to research topics is recommended.